Association of restless legs syndrome with malnutrition,inflammation and sleep quality in hemodialysis patients - HUANG Hua-xing; SHEN Liang-lan; ZHANG Fen; WANG Chen; FANG Xing-xing; CHEN Dong-mei (Linchuang shenzangbing zazhi)
Objective To observe the situation of maintenance hemodialysis(MHD) for chronic kidney disease( CKD) in patients with restless legs syndrome( RLS),analyze the incidence and severity of RLS and their relationship with malnutrition,inflammation and sleep quality,and to provide evidence for the prevention and treatment of RLS. Methods The 119 MHD patients were enrolled from the out-patient and in-patient,including 67 men and 52 women with age ranging from 25 to 78 years old( mean 60. 9 ± 13. 9years). The basic clinical characteristics and laboratory data were collected. RLS was diagnosed according to the criteria from International Restless Legs Syndrome Study Group. Malnutrition-inflammation( MIS) and Pittsburgh Sleep Quality Index( PSQI) were evaluated. Single factor Logistic regression analysis was used to analyze the related factors. Results All of the 119 patients were enrolled in the study,and there were 21 cases of RLS. MIS of the patients with or without RLS was similar( P > 0. 05). The PSQIS score in RLS group were significantly increased( P < 0. 05). The severity of RLS was positively correlated with PSQI( r =0. 445,P = 0. 006),white blood cells( r = 0. 427,P = 0. 008),and C reactive protein( CRP)( r =0. 418,P = 0. 010). There was no correlation between RLS and MIS( r = 0. 179,P = 0. 28). Conclusions The RLS in hemodialysis patients with CKD is related to the quality of sleep,and its severity was positively correlated with PSQI and some inflammatory parameters.